Os caminhos das políticas para a população negra no ensino superior: um estudo sobre a organização e a condução das ações afirmativas na Universidade Estadual de Ponta Grossa entre os anos 2013 a 2016 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
This research, based on the concepts of racism and affirmative action, presents the history of affirmative action in Brazil, unfolding in the policies of vacancy reservations in Brazilian public universities, focusing on the State University of Ponta Grossa (UEPG) in the period from 2013 to 2016. The main objective was to analyze how the applicability of the UEPG Vacancy Reserve Policy influenced the insertion of black people into the institution's student body. It was quantitative and qualitative research, organized into three chapters and based on the method of dialectical historical materialism, which contemplates, in its analytical arrangement, the structuring of society into social classes through the social practices of men, bringing history as a fundamental point for the understanding of reality.The use of the concepts of racism and affirmative action are included in the present object, as they figure on the materialistic structure of society conditioning the place of black people in Brazilian society. In short, racism is understood as a systematic form of "discrimination that has ‘race’ as its foundation, culminating in disadvantages or privileges, depending on the racial group to which they belong”. And affirmative action is understood as "focal policies that allocate resources to people belonging to groups discriminated against and victimized by socioeconomic exclusion regardless of the historical moment.” As a result of a historiographic analysis, the social contradictions of Ponta Grossa were observed, whether in the construction of the discourse of the historical constitution of the city or in the insertion of black people in the academic framework of the UEPG, which although progressive, has been occurring timidly. In the first moment due to the lack of public policies for basic education and in the second moment to the way the Vestibular exam is selected, through a minimum score. These results indicate the importance of discussion and implementation of policies that democratize access to education in Ponta Grossa, at all levels, as well as in Brazil.
Keywords: Ação afirmativa; Racismo; UEPG; Movimentos negros; História da Educação; Affirmative action; Racism; UEPG; Black Movement; History of Education; CNPQ::CIENCIAS HUMANAS::EDUCACAO